Studying the Structure Properties of Copper Nanoparticles Prepared by Chemical Reduction Method - Noora H. Al-Zobiadi; Ammar A. Habeeb; Awatif S. Jasim (Science and Technology Indonesia, 2023)
The chemical reduction method (CRM) can produce high purity nanoparticles, it is a down-top chemical method based on the principle of salt reduction, this method is used in this work to synthesis copper nanoparticals (CuPNs) by use different concentrations of copper nitrate. The properties of the prepared nanoparticles were studied by fourier transform infrared (FTIR) and ultraviolet-visible (UV-Vis) spectroscopy were used to measure the absorbance spectra of the produced particles. According to the scanning electron microscope (SEM), the particles’ diameters range from (61.64 to 49.25) nm. According to X-ray diffraction, the particles exhibit a face monoclinic crystal structure (FCC). According to the transmission electron microscope findings, the particles are asymmetrically spherical in shape.